A new strategy for the surgical management of RLN infiltrated by well-differentiated thyroid carcinoma - Boucek, Jan; Zabrodsky, Michal; Kuchar, Martin; Fanta, Ondrej; Skrivan, Jiri; Betka, Jan (BioMed research international, 2014)
Well-differentiated thyroid carcinoma (WDTC) represents the most common endocrine malignancy. Despite excellent prognoses exceeding 90% in 10-year follow-up, there are clinically controversial issues. One of these is extrathyroidal tumour extension invading recurrent laryngeal nerve (RLN). The spread outside of the thyroid parenchyma and invasion to the surrounding structures, classified as always T4a, are the most important negative prognostic factor for the WDTC. Conversely, resection of the RLN leads to vocal cord paralysis with hoarseness, possible swallowing problems, and finally decreased quality of life. We propose a new algorithm for intraoperative management based on the MACIS classification, which would allow swift status evaluation pre/intraoperatively and consider a possibility to preserve the infiltrated RLN without compromising an oncological radicality. In the case of a preoperative vocal cord paralysis (VCP) and confirmation of the invasive carcinoma, a resection of the RLN and the nerve graft reconstruction are indicated. Preoperatively, unaffected vocal cord movement and intraoperatively detected RLN infiltration by the invasive WDTC require an individual assessment of the oncological risk by the proposed algorithm. Preservation of the infiltrated RLN is oncologically acceptable only in specific groups of patients of a younger age with a minor size of primary tumour.
Keywords: trachea; ochrnutí hlasivek; Larynx; Middle Aged; Recurrent Laryngeal Nerve; Vocal Cord Paralysis; Adult; nádory štítné žlázy; Esophagus; kvalita života; Thyroid Neoplasms; larynx; nervus laryngeus recurrens; Humans; lidé středního věku; dospělí; Trachea; Quality of Life; ezofágus; lidé